2007
DOI: 10.1258/002367707779399482
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preweaning and postweaning housing on the behaviour of the laboratory mouse (Mus musculus)

Abstract: SummaryStandard housing for laboratory mice severely restricts natural behaviour and the control that the animal has over its environment. Providing the cage with objects is a method that has been used to both increase environmental complexity, promote the performance of natural behaviour and provide greater controllability for the animal. This method of furnishing cages has mostly been studied in adult animals, and little is known about the influence that the preweaning environment has on the behaviour of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
9
1
9
Order By: Relevance
“…The non-enriched non-infected group exhibited higher levels of allogrooming, corroborating the results of a study 42 in which mice kept in conventional environments expressed more allogrooming behaviors than mice kept in enriched environments. Similarly, we found that overall, infected mice exhibited less allogrooming than noninfected mice.…”
Section: Il-10 (Pg/ml)supporting
confidence: 85%
See 1 more Smart Citation
“…The non-enriched non-infected group exhibited higher levels of allogrooming, corroborating the results of a study 42 in which mice kept in conventional environments expressed more allogrooming behaviors than mice kept in enriched environments. Similarly, we found that overall, infected mice exhibited less allogrooming than noninfected mice.…”
Section: Il-10 (Pg/ml)supporting
confidence: 85%
“…A B C in non-enriched cages presented higher activity levels than mice kept in enriched cages 42 . The authors argued that mice explore cages more when no novelty is provided or maintain higher activity levels due to the impossibility of building nests or sleeping or due to increased attempts to escape from the cage.…”
Section: Il-10 (Pg/ml)mentioning
confidence: 84%
“…Specifically, females of these 2 strains (but not males) demonstrated significantly lower levels of thymocytes when living in an enriched cage as compared to the standard cage. In addition, the age at which the mouse is exposed to the enrichment and the duration of exposure may influence the effect on the animal . (p95)…”
Section: Effects Of Enrichmentmentioning
confidence: 99%
“…It is known that even subtle changes to the housing environment have long-lasting effects on neuronal structure, physiology and behaviour (Bayne, 2005;Benefiel et al, 2005;Marques and Olsson, 2007;Kulesskaya et al, 2011). Thus, performing within-litter and within-cage studies whenever possible is crucial to ensure that the changes in housing and fostering do not produce unintended artificial differences between experimental groups.…”
Section: Discussionmentioning
confidence: 99%